Evaluating ASEAN's Willing to Protect Migrant Workers: The Need for Reform - Emilia Fitriana Dewi; Ilham Nugraha; Agus Mulya Karsona; Dany Muhammad Athory Ramdlany; Umi Zuraida (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
The ten Member States of the Association of Southeast Asian Nations (ASEAN), as one of the economically influential regional organizations globally, are growing significantly in intraregional migration. Intraregional migration follows migrant workers across the country. This paper discusses the current state of migrant worker protection, especially in the context of the developments, challenges, and prospects among ASEAN countries. This paper aims to critically examine why ASEAN is seemingly hard to protect its migrant workers during its importance in the region’s economic development. This paper will first show the fundamental and pragmatic factors to the significance yet inadequate protection of migrant workers. Having analyzed the factors, the authors will argue about the ineffective principle of ‘The ASEAN Way’ in ensuring migrant workers’ protection by demonstrating ASEAN member countries’ response to migrant workers’ rights. In conclusion, this paper proposes institutional reform for ASEAN and provides further research on the issue. The protection of migrant workers is a key feature of the region’s labor market. It is expected that each country will have a better regulation to implement a fair labor migration system for the interests of governments, employers, and migrant workers.